Monges e mosteiros galegos em Portugal (séculos XII-XV) - Francisco Javier Pérez Rodríguez (Medievalista)
This paper identifies the Galician monasteries with real estate in the Kingdom of Portugal between the 12th and 15th centuries and analyses and characterizes such property. The policy of Portuguese monarchs regarding such property is also analysed while paying particular attention to political relations between Portuguese and Spanish kings. The ecclesiastical relations between Galician monasteries and the neighbouring kingdom are also subject of study: basically, the existing data at the archbishop's see of Braga –metropolitan see up to the Western Schism – and the pontifical authorization granted to Galician abbots to intervene in Portuguese affairs. Finally, a brief reference is made to the cultural and spiritual role of Galician monasteries in the neighbouring kingdom.